THE USE PICTURE AND PICTURE TEACHING METHOD IN READING COMPREHENSION NARRATIVE TEXT CLASS VIII SMP SWASTA DARUL ISTIQOMAH ACADEMIC YEAR 2022/2023 - Dessy Sahren; Wahyu Fatahillah; Raja Fauziah (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study deals with the use picture and picture teaching method in reading comprehension narrative text class VIII SMP Swasta Darul Istiqomah Academic Year 2022/2023. Its objective is to find out whether the use picture and picture teaching method has a significance effect in reading comprehension narrative text. Population used in this study of class VIII were 49 and samples used in this study were 49 students. The method used in this study is an experimental method with a one group as pretest and posttest design .This study was carried on using quantitate method. The data was analysed by using t-test.The researcher found the pretest mean = 54,49 , deviation standard = 6,14 and experienced an increase in the posttest mean = 77,75 deviation standart = 3,53. From this analysis, writer found that guided picture and picture method has significane in teaching reading comprehension narrative text. It can be proved by the result of the analysis showed that “